Modern weapons and military equipment for issue 01/2014 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Aged but UpgradedFrom Mall to FrontlineArmored EconomyPolish PL-01 combat vehicle concept rolled outRussia to establish 40 more army brigades by 2020Japan to develop stealth-detecting long-range radarTurkey selects Chinese HQ-9 SAM for T-Loramids